Conceiving the Future : Pronatalism, Reproduction, and the Family in the United States, 1890-1938 - Lovett, Laura L. (Book collections on Project MUSE., 2007)
Through nostalgic idealisations of motherhood, family, and the home, influential leaders in early twentieth-century America constructed and legitimated a range of reforms that promoted human reproduction. This book looks closely at the ideologies of five influential American figures: Mary Elizabeth Lease's maternalist agenda, Florence Sherbon's eugenic 'fitter families' campaign, George H. Maxwell's 'homecroft' movement of land reclamation and home building, Theodore Roosevelt's campaign for conservation and country life, and Edward Alsworth Ross's sociological theory of race suicide and social control.